Intradialytic exercise and postural control in patients with chronic kidney disease undergoing hemodialysis - Carla Oliveira Carletti; Clara Suemi da Costa Rosa; Giovana Damasceno e Souza; Ariane Pereira Ramirez; Célio Guilherme Lombardi Daibem; Henrique Luiz Monteiro
Abstract Introduction: Exercise promotes physiological improvements that reflect better quality of life and survival among chronic kidney disease patients. However, little is known about the effect of exercise on postural control of hemodialysis patients. Objective: To evaluate the effect of intradialytic aerobic exercise on postural balance in patients on hemodialysis. Methods: a pilot study with seven individuals was conducted at the Hemodialysis Center of Bauru State Hospital. The Berg Balance Scale evaluated balance and postural balance was evaluated by the force platform Advance Mechanical Technology Inc. (AMTI - AccuGait). Trunk mean sway amplitude in the anterior-posterior (AP) and medial-lateral (ML) directions and mean velocity in the AP and ML directions were assessed. Secondary outcomes about functional capacity and body composition (DEXA) were evaluated. The aerobic exercise was performed with a ergometric bicycle during the first two hours of hemodialysis session for 50-60 minutes (BORG >12), three times a week for 12-weeks. Results: Four men and three women, 52.86 ± 11.08 years, participated in the study. There was no difference between pre and post-test of postural balance outcomes. Although the results were not statistically significant, except for the lean body mass and leg lean mass, the presented pilot study suggests improved functional balance and lower limb strength. Conclusion: The 12-weeks of aerobic exercise protocol during hemodialysis despite inducing gains in lean body mass and leg lean mass, was not able to promote improvements in postural control of chronic renal failure patients on hemodialysis.